2012
DOI: 10.1172/jci62308
|View full text |Cite
|
Sign up to set email alerts
|

Brown adipose tissue regulates glucose homeostasis and insulin sensitivity

Abstract: Brown adipose tissue (BAT) is known to function in the dissipation of chemical energy in response to cold or excess feeding, and also has the capacity to modulate energy balance. To test the hypothesis that BAT is fundamental to the regulation of glucose homeostasis, we transplanted BAT from male donor mice into the visceral cavity of age-and sex-matched recipient mice. By 8-12 weeks following transplantation, recipient mice had improved glucose tolerance, increased insulin sensitivity, lower body weight, decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
871
4
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 999 publications
(951 citation statements)
references
References 44 publications
41
871
4
11
Order By: Relevance
“…However, we did not observe significant changes in circulating IL-6 levels 20 weeks post BAT transplantation in the current study (Supplementary information, Figure S1N-S1O), which is consistent with a recent report that subcutaneous BAT transplantation significantly reduced diabetes-induced inflammation, as evidenced by low levels of the proinflammatory cytokines IL-6 and TNF-α in the epididymal WAT [9]. This discrepancy may be due to the following differences of the approaches used in the present prevention study and the work by Stanford et al [8]: the post-BAT-transplantation period (~20 weeks vs 12 weeks), the site of transplantation (subcutaneous vs visceral cavity), and the ages of the donors and recipients (6 weeks vs 12 weeks).…”
Section: Wwwcell-researchcom | Cell Research Xiaomeng Liu Et Al 853supporting
confidence: 91%
See 1 more Smart Citation
“…However, we did not observe significant changes in circulating IL-6 levels 20 weeks post BAT transplantation in the current study (Supplementary information, Figure S1N-S1O), which is consistent with a recent report that subcutaneous BAT transplantation significantly reduced diabetes-induced inflammation, as evidenced by low levels of the proinflammatory cytokines IL-6 and TNF-α in the epididymal WAT [9]. This discrepancy may be due to the following differences of the approaches used in the present prevention study and the work by Stanford et al [8]: the post-BAT-transplantation period (~20 weeks vs 12 weeks), the site of transplantation (subcutaneous vs visceral cavity), and the ages of the donors and recipients (6 weeks vs 12 weeks).…”
Section: Wwwcell-researchcom | Cell Research Xiaomeng Liu Et Al 853supporting
confidence: 91%
“…While this manuscript was in preparation, an independent study by Stanford et al [8] reported that BAT transplantation improved glucose homeostasis, and that the beneficial effect might be mediated by IL-6 as transplantation of BAT dissected from IL-6-knockout (KO) mice did not improve glucose metabolism. However, we did not observe significant changes in circulating IL-6 levels 20 weeks post BAT transplantation in the current study (Supplementary information, Figure S1N-S1O), which is consistent with a recent report that subcutaneous BAT transplantation significantly reduced diabetes-induced inflammation, as evidenced by low levels of the proinflammatory cytokines IL-6 and TNF-α in the epididymal WAT [9].…”
Section: Wwwcell-researchcom | Cell Research Xiaomeng Liu Et Al 853mentioning
confidence: 99%
“…As BAT is known to protect animals from the cold (Stanford et al., 2013), we induced a cold challenge and found that body temperature was preserved better in RGS14 KO than in WT littermates (Figure 2f,g), with basal body temperatures similar in both the dark and the light cycles. In addition, mock surgery of BAT transplant in RGS14 KO and its WT littermates, that is, conducting the surgical procedure, but not removing BAT from RGS14 KO, did not alter the pattern of thermogenic function protection in RGS14 KO (Figure 2f,g).…”
Section: Resultsmentioning
confidence: 94%
“…The BAT is a protective mechanism of recent interest. BAT enhances energy metabolism and protects against cold exposure and obesity (Stanford et al., 2013). A novel model to investigate the role of BAT in healthful aging and lifespan is the mouse model of the disruption of the regulator for G protein signaling 14 (RGS14), which has increased BAT.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of whether BAT has a major physiological role in body weight regulation in mice and humans, there is no question that expanding the activity of brown fat, beige fat or both in mice through genetic manipulation, drugs or transplantation suppresses metabolic disease [15][16][17]47,[60][61][62][63] (Table 1). These results imply that counterregulatory mechanisms (for example, increased food intake), which might have been predicted to offset the effects of expanded BAT activity to preserve energy balance, are not fully effective in mice.…”
Section: Regulation Of Brown and Beige Adipocytes By Prdm16mentioning
confidence: 99%